Perlindungan Hukum Terhadap Anak Yang Berada Di Wilayah Perang Menurut Konvensi Jenewa 1949 Dengan Protokol Tambahan 1977 - Amini, Intan; Pebrianto, Dony Yusra (Uti Possidetis: Journal of International Law, 2022)
This article discusses how to protect children who are in areas of armed conflict. Protection of children has been regulated in the Geneva Conventions of 1949, Additional Protocols 1977, International Convention on The Rights of Childs 1989, Optional Protocol on Involvent of Children in Armed Conflict 2000. However, the parties to the conflict still violate the principle of distinction, the principle of limitation, the principle of balance, and the principles of protection that apply in international humanitarian law. In fact, Humanitarian Law prohibits civilians from being used as objects of violence and must be given protection from all matters relating to war. Meanwhile, combatants can be used as objects of violence during war, but they must still be given protection when they are prisoners of war. As a form of state responsibility, criminal sanctions and compensation need to be applied to ensure legal certainty and provide justice for the parties who are victims according to humanitarian law.